Rhetorical employment of the color in fictional film - Abdulmahdi, Muneer Salah (Al-Adab Journal, 2022)
The cinema has been in many developments levels since it begins, on both levels the technical and the artistic level, which helped to convert it from being a manufacturing process to art, among all these developments, the color was discovered and its first existing in to the cinema, which use to base on two colors white and black basically, the ability to add the color wasn’t exist in the first 3 decades of the cinema age, and according to the color importance to be inside the cinema world was an essential need, and that what motivate the ones who work in cinema starts their experiments to bring this element to the film. After a while of the color existing in the cinema, quickly the ones who works in this field where aware about how its important and effective on the audience, end up being one of the very important elements in the cinema language, the color stopped being only just a color in the simple meaning of the word inside a frame, but has its own special philosophy which makes it very different than the other image element. The color works on creating the mane and the specific feeling, reserving the dramatic and the rhetoric meaning, which the work creators want to deliver to the audience inside the cinematic image structure.